2013
DOI: 10.1177/1045389x12471867
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and evaluation of effect of dehydration on vibration characteristics of silver-electroded ionic polymer–metal composite actuator

Abstract: Theoretical and experimental investigation of dehydration loss of ionic polymer–metal composite actuator is important to evaluate the stability, accuracy, and effectiveness of actuation. An ionic polymer–metal composite actuator of silver electrode has been analyzed to demonstrate the effect of dehydration on vibration characteristics during actuation. Experiment is conducted in cantilever configuration under direct current potential, and the bending and vibration characteristics are measured by Laser Vibromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The tip deflections data are taken for 30 seconds for each input voltage. It is observed that system exhibits a typical nonlinear behavior as various non-linear terms are present in the temporal equation of motion (10).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The tip deflections data are taken for 30 seconds for each input voltage. It is observed that system exhibits a typical nonlinear behavior as various non-linear terms are present in the temporal equation of motion (10).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The observation reveals that with AC input, the actuator can operate for a longer time period than same DC input voltage. The relationship between dehydration of water molecules form IPMC strip (lossfactor) in terms of input voltage (V) and time period (t) as given by [10] and can be represented by Eq. (3) is shown in Figure 3.…”
Section: Calculation Of Solvent Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown the concentration, intrinsic properties, and moving directions of cations have a dominant effect on the behaviour of the IPMC actuator. Besides, the dynamic motion of IPMC could be a function of driving voltage amplitude, frequency, and device geometry, thereby adding the complication of its performance investigation [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%